2008 IEEE International Conference on Wireless and Mobile Computing, Networking and Communications 2008
DOI: 10.1109/wimob.2008.28
|View full text |Cite
|
Sign up to set email alerts
|

Multi-hop Cross-Layer Design in Wireless Sensor Networks: A Case Study

Abstract: Cross-layer design has been proposed as a promising paradigm to tackle various problems of wireless communication systems. Recent research has led to a variety of protocols that rely on intensive interaction between different layers of the classical layered OSI protocol architecture. These protocols involve different layers and introduce new ideas how layers shall communicate and interact. In existing cross-layer approaches, the violation of the OSI architecture typically consists in passing information betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In [10], authors propose a multi-hop communication model in which information can be exchanged between different layers of multiple stations. In experimental environment they implemented this additional feature in WiseMAC protocol.…”
Section: Details Of Cross Layer Approachmentioning
confidence: 99%
“…In [10], authors propose a multi-hop communication model in which information can be exchanged between different layers of multiple stations. In experimental environment they implemented this additional feature in WiseMAC protocol.…”
Section: Details Of Cross Layer Approachmentioning
confidence: 99%
“…These performance gains can be in the form of energy efficiency, reduced contention, better routing decisions or improved reliability. Research has shown that cross-layer designs can have a beneficial effect on the performance of wireless networks [7072]. Taking a step back and looking at the protocol stack as a whole can help to focus on new solutions to wireless communication issues that a cross-layer approach can alleviate.…”
Section: The Case For Cross-layer Designmentioning
confidence: 99%
“…Such violation of a layered architecture is cross layer design interfaces are created between the layers in the CLD [9][10][11]. The most suitable design for communication in wireless networks is Cross Layer Design (CLD).…”
Section: Related Workmentioning
confidence: 99%